Organic acids and protein compounds causing the photoluminescence properties of natural rubber membranes and the quenching phenomena from Au nanoparticle incorporation - Cabrera, Flavio C. [UNESP]; Agostini, Deuber L. S. [UNESP]; Santos, Renivaldo J. dos [UNESP]; Guimaraes, Francisco E. G.; Guerrero, Ariel R.; Aroca, Ricardo F.; Job, Aldo E. [UNESP] (Wiley-Blackwell, 2014)
Natural rubber membranes were fabricated using latex from Hevea brasiliensis trees (clone RRIM 600) by casting, and controlling the time and temperature of thermal treatment. Three temperatures were used: 65, 80 and 120 degrees C and the corresponding annealing times of 6, 8, 10 and 12h. The centrifugation of the latex produces the constituent phases: solid rubber (F1), serum or protein components (F2) and bottom fraction (F3). The photoluminescence properties could be correlated with organic acid components of latex. Natural rubber membranes were used as the active substrate (reducing agent) for the incorporation of colloidal Au nanoparticles synthesized by in situ reduction at different times. The intensity of photoluminescence bands assigned to the natural rubber decreases with the increase in amount of nanoparticles present on the membrane surface. It can be assumed that Au nanoparticles may be formed by reduction of the Au cation reacting with functional groups that are directly related to photoluminescence properties. However, the quenching of fluorescence may be attributed to the formation of a large amount of metal nanostructures on the natural rubber surface. Copyright (c) 2014 John Wiley & Sons, Ltd.
Keywords: Natural rubber (NR); UV-Vis Spectroscopy; casting method; photoluminescence spectroscopy; latex